(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Business ethics is an essential aspect of any startup. It is a set of moral principles that guide the behavior and actions of individuals in the organization. Effectiveness in business ethics ensures that the company makes decisions that align with its values, mission, and vision and can improve employee morale and productivity while reducing legal risks. In our study, the composite weighted mean of the enterprise’s core values was 4.32 for singles and 4.28 for married people, which were both interpreted as strongly agreeing. For day-to-day decisions, the weighted mean by single is 4.68 and married is 4.28, both interpreted strongly agree, while the conflict of interest by single is 4.36 and married is 4.68, both interpreted strongly agree, and the company involved in the community is 4, interpreted agree, and married is 4.64, interpreted strongly agree. In conclusion, the level of effectiveness of business ethics is critical for running a successful start-up. A development plan for a startup should include a strong emphasis on ethical behavior and practices. This may include implementing a code of conduct or ethics policy, providing ethics training for employees, conducting regular audits to ensure compliance, and regularly reviewing and updating policies and procedures to reflect changing ethical standards and practices. By prioritizing ethics, a startup can build a strong foundation for long-term success and growth.